The Cataphoric Pronoun in Biblical Hebrew - Garr, W. Randall (Journal of Semitic studies, 2022)
The cataphoric pronominal construction has long been recognized in Biblical Hebrew. It is formally redundant, consisting usually of a bound third-person object pronoun and subsequent, coreferential noun or noun phrase. A standard, familiar example is ‘she saw him, the child’ in Exod. 2:6. The following article attempts a comprehensive account of this grammatical construction, including its semantic value, its discourse role, and especially its pragmatic functions in a number of contexts. This article also compares its appearance in the Septuagint, the Samaritan Pentateuch, the Dead Sea scrolls and the Masoretic text. It concludes that, while the cataphoric pronominal construction was a genuine (i.e. non-borrowed) feature of Biblical Hebrew, it was most favoured by the Masoretic tradition in the later Biblical books even though the construction was never grammaticalized.